Penerapan Pembelajaran IPA Berbasis Outdoor Education untuk Memperkuat Pengalaman Belajar Konsep-konsep Alam di SDN 056021 Pematang Tengah - Miftahul Aisyiyah Bakti; Amelia Alifah Sagala; Ade Kurnia Sari; Syahrial (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the application of outdoor education-based Natural Science (IPA) learning in strengthening students' learning experiences regarding natural concepts. Outdoor learning provides opportunities for students to be directly involved with the surrounding environment, so that science concepts become more real and easier to understand. The study was conducted using a qualitative method with a case study approach on fifth grade students at SDN 056021 Pematang Tengah. Data were collected through participant observation, in-depth interviews. The results of the study showed that outdoor education-based science learning increased learning motivation, active student involvement, and better understanding of the natural concepts taught. This study recommends the integration of outdoor education into the science curriculum to improve the quality of students' learning experiences and prepare them to become individuals who care about the environment.